Analisis Overreaction dan Likuiditas Terhadap Price Reversal Saham-Saham Syariah di Industri Manufaktur Pada Masa Pandemi Covid-19 di Indonesia - Siti Komariah; Dziky Ghifari Dimyati (Journal of Economic, Bussines and Accounting (COSTING), 2024)
News about the covid-19 pandemic that emerged in Indonesia at the beginning of the pandemic period in 2020 received different responses from investors. The graph of the Indonesia Sharia Stock Index (ISSI) shows that there is an excessive response from investors in response to news about the covid-19 pandemic, this overreaction is called overreaction which has provoked aprice reversal in the next period. This study aims to analyze the effect of overreaction and liquidity on price reversal during the peak of the covid-19 pandemic in Indonesia. The sample in this study is the ISSI manufacturing sector, there are 59 companies that meet the sample criteria. The research period is in 2019-2022. This study uses secondary data where the data used is daily data on Islamic stocks engaged in the manufacturing sector and ISSI data. The data analysis technique used in this study is multiple linear regression with panel data using Eviews 12 software. The results showed that stock price reversals occurred at two important moments during the covid-19 pandemic, while the results of hypothesis testing showed that overreaction and liquidity variables had an effect on price reversal. Keywords: Overreaction, Liquidity, Price Reversal, ISSI, Covid-19